The Effect Of Ergonomic Exercise And Alternate Nostril Breathing Exercise On Reduction Blood In Elderly With Hypertension - Akbar Herlambang; Dahrizal; Nehru Nugroho (Poltekkes Kemenkes Banten, 2026)
Background: Hypertension is one of the most common non-communicable diseases (NCDs) and is known as a silent killer. It is a major health problem due to its role as a risk factor for stroke and heart disease in the elderly. In Bengkulu City, the prevalence of hypertension is considered high, with 261,621 individuals diagnosed according to the 2022 Health Office data. Objective: This study aims to determine the effect of ergonomic exercise and alternate nostril breathing exercise on reducing blood pressure in elderly people with hypertension at the Lingkar Timur Public Health Center, Bengkulu City. Method: This research employed a quantitative approach with a pre-experimental design, using a pre-post test design with intervention group. A total of 43 participants were selected using random sampling based on inclusion criteria: aged 55–65 years with blood pressure ≥140/90 mmHg. Instrument reliability was tested by conducting two blood pressure measurements. Results: The results showed a significant difference in the average systolic and diastolic blood pressure before and after the intervention. Statistical analysis using the Wilcoxon Signed Rank Test yielded a p-value of 0.000 (p ≤ 0.05), indicating a significant effect of the intervention on blood pressure reduction. Conclusion: Ergonomic exercise and alternate nostril breathing exercise are effective in lowering blood pressure in elderly individuals with hypertension. These interventions can be applied independently by the elderly as a non-pharmacological effort to control blood pressure.